2021
DOI: 10.3389/fnins.2021.621145
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Mechanisms of Tinnitus: A Perspective From Functional Magnetic Resonance Imaging

Abstract: Tinnitus refers to sound perception in the absence of external sound stimulus. It has become a worldwide problem affecting all age groups especially the elderly. Tinnitus often accompanies hearing loss and some mood disorders like depression and anxiety. The comprehensive adverse effects of tinnitus on people determine the severity of tinnitus. Understanding the mechanisms of tinnitus and related discomfort may be beneficial to the prevention and treatment, and then getting patients out of tinnitus distress. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 92 publications
0
34
0
Order By: Relevance
“…In the present study, we found significantly changed (increased or decreased) intranetwork FC within the AUN, aDMN, LFPN, lVN, DAN, and SN in the EG and/or IG compared with the HC group. As an auditory phenomenon, tinnitus has been repeatedly reported to be associated with alterations in the AUN (or auditory regions; Cai, Li, Yang, & Zhang, 2019; Hu et al, 2021; Husain, 2016; Husain et al, 2011; Lan et al, 2021; Schmidt, Akrofi, Carpenter‐Thompson, & Husain, 2013), which indicates the important role of the AUN in tinnitus generation. As the center of the primary auditory cortex, the STG is also considered to be an important multisensory functional brain region that integrates visual, auditory, and language information (Mtui, Gruener, & Dockery, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found significantly changed (increased or decreased) intranetwork FC within the AUN, aDMN, LFPN, lVN, DAN, and SN in the EG and/or IG compared with the HC group. As an auditory phenomenon, tinnitus has been repeatedly reported to be associated with alterations in the AUN (or auditory regions; Cai, Li, Yang, & Zhang, 2019; Hu et al, 2021; Husain, 2016; Husain et al, 2011; Lan et al, 2021; Schmidt, Akrofi, Carpenter‐Thompson, & Husain, 2013), which indicates the important role of the AUN in tinnitus generation. As the center of the primary auditory cortex, the STG is also considered to be an important multisensory functional brain region that integrates visual, auditory, and language information (Mtui, Gruener, & Dockery, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…the auditory cortex (AC), as well as other non-auditory areas of the brain, leading to thi perceived sound [15,16]. There are also ototoxic medications such as aspirin, cisplatin aminoglycosides, and loop diuretics that have been associated with tinnitus [17,18].…”
Section: Technology Overview Of Rtmsmentioning
confidence: 99%
“…It can be caused by several different underlying conditions that affect a wide range of structures between the ear and the brain itself, leading to variability in clinical manifestations. It has been suggested that damage to structures such as the auditory nerve or hair cells within the cochlea can lead to changes in plasticity that enhance the activity in the auditory cortex (AC), as well as other non-auditory areas of the brain, leading to this 2 of 21 perceived sound [15,16]. There are also ototoxic medications such as aspirin, cisplatin, aminoglycosides, and loop diuretics that have been associated with tinnitus [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Tinnitus originates in the auditory system, but changes in functional connectivity and neuronal activity of non-auditory systems in uence the perception, persistence and severity of tinnitus (8).…”
Section: Background and Rationale {6a}mentioning
confidence: 99%